A measurement of Omega from the North American test flight of BOOMERANG - Melchiorri, A; Ade, P; Bernardis, P; Bock, J; Borrill, J; Boscaleri, A; Crill, B; Troia, G; Farese, P; Ferreira, P; Ganga, K; Gasperis, G; et al. (1999)
We use the angular power spectrum of the Cosmic Microwave Background, measured during the North American test flight of the BOOMERANG experiment, to constrain the geometry of the universe. Within the class of Cold Dark Matter models, we find that the overall fractional energy density of the universe, Omega, is constrained to be 0.85 < Omega < 1.25 at the 68% confidence level. Combined with the COBE measurement and the high redshift supernovae data we obtain new constraints on the fractional matter density and the cosmological constant.